TNF-α Autocrine Feedback Loops in Human Monocytes: The Pro- and Anti-Inflammatory Roles of the TNF-α Receptors Support the Concept of Selective TNFR1 Blockade In Vivo. (22nd September 2016) - Gane, Jennie M.; Stockley, Robert A.; Sapey, Elizabeth
Abstract : Selective TNFR1 blockade in inflammatory diseases is emerging as a clinical strategy. We studied the roles of the two TNF- α receptors, TNFR1 and TNFR2, in human monocytes, the principal producer of TNF- α and central to many TNF- α driven diseases. We hypothesised that TNF- α has pro- and anti-inflammatory effects on monocytes, occurring differentially via TNFR1 and TNFR2. Monocytes were isolated from healthy human subjects and exposed to LPS, plus/minus the addition of blocking antibodies to TNF- α or its receptors. Pro- and anti-inflammatory cytokine production was quantified using real-time PCR and ELISAs. Cell surface expression of TNFR1/2 was measured by flow cytometry. We demonstrated that monocytes vary in the expression patterns of TNFR1 and TNFR2. Autocrine binding of TNF- α led to sustained upregulation of proinflammatory cytokines via TNFR1. In contrast, autocrine binding via TNFR2 upregulated the anti -inflammatory cytokine, IL-10, without proinflammatory effect. TNFR2 was responsible for binding soluble TNF- α secreted by monocytes, clearing the cytokine from the pericellular environment. TNFR1 blockade did not change the cell surface expression of TNFR2, leaving this receptor free to upregulate IL-10. These novel results support the concept of selective TNFR1 blockade in vivo in order that positive anti-inflammatory effects of TNF- α can be retained via TNFR2 ligation.